Ledipasvir and sofosbuvir fixed-dose combination with and without ribavirin for 12 weeks in treatment-naive and previously treated Japanese patients with genotype 1 hepatitis C: an open-label, randomised, phase 3 trial. Issue 6 (June 2015) - Mizokami, Masashi; Yokosuka, Osamu; Takehara, Tetsuo; Sakamoto, Naoya; Korenaga, Masaaki; Mochizuki, Hitoshi; Nakane, Kunio; Enomoto, Hirayuki; Ikeda, Fusao; Yanase, Mikio; Toyoda, Hidenori; Genda, Takuya; et al.
Summary Background Compared with other countries, patients with chronic hepatitis C infection in Japan tend to be older, have more advanced liver disease, and are more likely to have been previously treated for hepatitis C. We aimed to assess the efficacy and safety of an all-oral, fixed-dose combination of the hepatitis C virus NS5A inhibitor ledipasvir and the NS5B nucleotide polymerase inhibitor sofosbuvir with and without ribavirin for 12 weeks in treatment-naive and previously treated Japanese patients with chronic genotype 1 hepatitis C virus infection. Methods In this randomised, open-label study, we enrolled patients from 19 clinical Japanese centres. Patients were randomly assigned (1:1) to receive either ledipasvir (90 mg) and sofosbuvir (400 mg) or ledipasvir, sofosbuvir, and ribavirin (dosed according to the Japanese Copegus product label—ie, patients ≤60 kg received 600 mg daily, patients >60 kg to ≤80 kg received 800 mg daily, and patients >80 kg received 1000 mg daily) orally once daily for 12 weeks. After completion or early discontinuation of treatment, patients were followed up off-treatment for 24 weeks. Eligible patients were at least 20 years of age with chronic genotype 1 hepatitis C virus infection with serum hepatitis C virus RNA concentrations of at least 5 log10 IU/mL, creatinine clearance of at least 1·0 mL/s, and a platelet count of at least 50 × 109 per L. An interactive web response system was used to manage patient randomisation and treatment assignment. Randomisation was stratified by the presence or absence of cirrhosis for treatment-naive patients and stratified by presence or absence of cirrhosis and by previous treatment category (relapser or breakthrough, non-responder, or interferon-intolerant) for previously treated patients. Within each strata, patients were sequentially assigned to either treatment with ledipasvir-sofosbuvir or ledipasvir-sofosbuvir plus ribavirin in a 1:1 ratio with block size of 4. The primary endpoint was sustained virological response 12 weeks after completion of treatment (SVR12) assessed in all patients who were randomly assigned and received at least one dose of study drug; safety outcomes were assessed in all patients who received at least one dose of study drug. This trial is registered with ClinicalTrials.gov, number NCT01975675. Findings Between Oct 15, 2013 and Dec 13, 2013, 341 patients were randomly assigned to treatment groups and received at least one dose of study treatment. SVR12 was achieved in all 171 (100%) patients (83 of 83 treatment naive and 88 of 88 treatment experienced) receiving ledipasvir-sofosbuvir (95% CI 98–100) and 167 (98%) of 170 patients (80 of 83 treatment naive and 87 of 87 treatment experienced) receiving ledipasvir-sofosbuvir plus ribavirin (95% CI 95–100). Of the 76 patients with baseline NS5A resistant variants, 75 (99%) achieved SVR12. Two (1·2%) of 170 patients in the ledipasvir-sofosbuvir plus ribavirin group discontinued treatment because of adverse events. The most common adverse events were nasopharyngitis (50 [29·2%] of 171), headache (12 [7·0%] of 171), and malaise (nine [5·3%] of 171) in patients receiving ledipasvir-sofosbuvir; and nasopharyngitis (40 [23·5%] of 170), anaemia (23 [13·5%] of 170), and headache in those receiving ledipasvir-sofosbuvir and ribavirin (15 [8·8%] of 170). Interpretation Although existing regimens for the treatment of hepatitis C virus are effective for many patients, medical needs remain unmet, particularly in Japan where the population with hepatitis C virus genotype 1 is generally older and treatment-experienced, with advanced liver disease. The efficacy, tolerability, and absence of drug–drug interactions of ledipasvir-sofosbuvir suggest that it could be an important option for treatment of genotype 1 hepatitis C virus in Japanese patients. Funding Gilead Sciences.